2016
DOI: 10.1007/s11223-016-9812-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental-Numerical Study of Tensile Strength of the High-Strength Steel S690QL at Elevated Temperatures

Abstract: Ïðåäñòàâëåíû ðåçóëüòàòû ðàñ÷åòíî-ýêñïåðèìåíòàëüíîãî àíàëèçà âëèÿíèÿ òåìïåðàòóðû íà ìåõàíè÷åñêèå ñâîéñòâà âûñîêîïðî÷íîé êîíñòðóêöèîííîé ñòàëè S690QL. Îïðåäåëåíà ìàêñèìàëüíàÿ òåìïåðàòóðà ïðè ñòàòè÷åñêèõ èñïûòàíèÿõ íà ðàñòÿaeåíèå, ïðè êîòîðîé äàííàÿ ñòàëü ñîõðàíÿåò âûñîêèå ìåõàíè÷åñêèå õàðàêòåðèñòèêè. Ñòàòè÷åñêèå èñïûòàíèÿ íà ðàñòÿaeåíèå ïðîâîäèëèñü ïðè ïÿòè ðàçëè÷íûõ òåìïåðàòóðàõ â äèàïàçîíå 20…550°Ñ. Ïîëó÷åííûå ýêñïåðèìåíòàëüíûå äàííûå ñðàâíèâàëèñü ñ ðåçóëüòàòàìè êîíå÷íîýëåìåíòíûõ ðàñ÷åòîâ ïóòåì ïîñòðîåíèÿ ñîîò… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In fact, the results show a quick reduction in the ultimate tensile strength as soon as 600 °C is exceeded, but the full collapse occurs at 650 °C and above. A similar tendency was discovered in the previous study on the influence of high temperatures on tensile strength of the structural steel S690QL [23], where it was concluded that a decrease in tensile properties occurs at 450 °C. The tensile strength decrease with a temperature increase is expected due to recrystallization and softening.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, the results show a quick reduction in the ultimate tensile strength as soon as 600 °C is exceeded, but the full collapse occurs at 650 °C and above. A similar tendency was discovered in the previous study on the influence of high temperatures on tensile strength of the structural steel S690QL [23], where it was concluded that a decrease in tensile properties occurs at 450 °C. The tensile strength decrease with a temperature increase is expected due to recrystallization and softening.…”
Section: Resultssupporting
confidence: 88%
“…The stress integration algorithm for large strain deformations in the isotropic plasticity based on the multiplicative decomposition of the deformation gradient using the logarithmic strains is given in details in [23]. Due to the low plasticity and ultra-high strength of the tested steel it can be concluded that the visible necking is missing up to the temperatures of 650 ºC.…”
Section: Large Strain Elastic-plastic Analysismentioning
confidence: 99%
“…The cooling time in that temperature range can be calculated according to different expressions, as well as determined experimentally. Knowing that cooling time and relevant material properties, enables prediction of characteristics of the welded joint and the heat affected zone [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The cooling time, in that temperature range, can be calculated according to different expressions, as well as determined experimentally. Knowing that cooling time and relevant material properties enables prediction of characteristics of the welded joint and the heat affected zone [22][23][24].…”
Section: Introductionmentioning
confidence: 99%